2006
DOI: 10.1002/jhet.5570430605
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition reactions of n‐alkylated 2‐aminobiphenyls to carbazole and phenanthridine

Abstract: + + + 1a-c 3 4 5 6 2 5 R 2 CaO CaOThermal cyclization reactions were examined by passing vapors of N-alkylated 2-aminobiphenyls 1a-c and 2 over calcium oxide at 450-600°C under nitrogen carrier gas. The reactions yielded 9methylcarbazole 3, carbazole 4, phenanthridine 5 and phenanthrene 6. The major product for the reactions of 1a, 1b and 2 was phenanthridine 5 while that of 1c was carbazole 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Rather than relying on the co‐polymerization of two dissimilar molecular precursors, we designed a molecular building block bearing a 9‐methyl‐9 H ‐carbazole substituent as an internal reactive moiety ( 1 in Figure ). Previous work demonstrated that the thermally induced rearrangement of 9‐methyl‐9 H ‐carbazole at T >500 °C on a CaO support leads to a product mixture containing both phenanthridine and carbazole . Once incorporated into the edges of a fully fused GNR, the electron‐rich 9‐methyl‐9 H ‐carbazole could thus be converted into an electron‐deficient phenanthridine substituent through a thermally induced ring‐expansion/dehydrogenation reaction.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Rather than relying on the co‐polymerization of two dissimilar molecular precursors, we designed a molecular building block bearing a 9‐methyl‐9 H ‐carbazole substituent as an internal reactive moiety ( 1 in Figure ). Previous work demonstrated that the thermally induced rearrangement of 9‐methyl‐9 H ‐carbazole at T >500 °C on a CaO support leads to a product mixture containing both phenanthridine and carbazole . Once incorporated into the edges of a fully fused GNR, the electron‐rich 9‐methyl‐9 H ‐carbazole could thus be converted into an electron‐deficient phenanthridine substituent through a thermally induced ring‐expansion/dehydrogenation reaction.…”
Section: Figurementioning
confidence: 99%
“…Here, the bottom-up synthesis of chevron GNRs decorated with reactivef unctional groups derived from 9-methyl-9H-carbazole is reported. [7] Once incorporated into the edges of af ully fused GNR, the electron-rich 9-methyl-9H-carbazole could thus be converted into an electron-deficient phenanthridine substituent through at hermally induced ring-expansion/dehydrogenation reaction. The selective chemical edge-reconstruction of carbazole-substitutedc hevron GNRsr epresents ap ractical strategyf or the controlled fabrication of spatially defined GNR heterostructures from asingle molecular precursor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To gain insight into the reaction mechanism, we prepared potential intermediate N-benzyl-2- (1,3-diphenyl-1H-pyrazol-5yl)aniline from 2-(1,3-diphenyl-1H-pyrazol-5-yl)aniline and benzaldehyde 4 a [14] and treated it under the optimal condition Scheme 3. To study the mechanism by using probable intermediate Scheme 4.…”
Section: Resultsmentioning
confidence: 99%
“…By a thermally activated ring expansion/dehydrogenation reaction, the electron-rich carbazole could be converted into the electron-deficient phenanthridine [120]. In this work, authors succeeded to partially convert the carbazole groups into phenanthridine, opening the way towards the fine tuning of the materials bandgaps by the presence of electron-rich and electron-poor groups onto the same structures (see Figure 20B).…”
Section: Coupling Modes Used For the Design Of 1d Macromolecular Omentioning
confidence: 98%